2011
DOI: 10.1159/000325172
|View full text |Cite
|
Sign up to set email alerts
|

The Concurrent Validity and Sensitivity of Change of the German Version of the Health of the Nation Outcome Scales in a Psychiatric Inpatient Setting

Abstract: Background: The Health of the Nation Outcome Scales (HoNOS) were developed to assess the severity of a mental illness. They are used as outcome measures in different countries, and are meanwhile translated from the original English version into many languages, among others into German (HoNOS-D). We conducted a study in order to estimate the concurrent validity and sensitivity to change using clinical parameters as ICD-10 diagnoses, as well as the Clinical Global Impression Scale (CGI), and the Association for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
0
6
1
1
Order By: Relevance
“…The HoNOS-scores from both countries did not differ substantially from what has been found in other inpatient studies [40-46], but due to the structural and demographic differences between the two countries, the difference may seem unexpectedly small. A partly explanation may be different attitudes towards admitting mental problems: In a comparative study, Angermeyer et al [10] found that Russian respondents had a stronger tendency to consider mental disorders as self-inflicted.…”
Section: Discussioncontrasting
confidence: 47%
“…The HoNOS-scores from both countries did not differ substantially from what has been found in other inpatient studies [40-46], but due to the structural and demographic differences between the two countries, the difference may seem unexpectedly small. A partly explanation may be different attitudes towards admitting mental problems: In a comparative study, Angermeyer et al [10] found that Russian respondents had a stronger tendency to consider mental disorders as self-inflicted.…”
Section: Discussioncontrasting
confidence: 47%
“…shown to be related to illness severity 25,26 . Every item is rated on a Likert-style scale, ranging from 0 (no problem) to 4 (severe problem), yielding a total score from 0 to 48.…”
Section: Socio-demographic and Clinical Exposuresmentioning
confidence: 99%
“…were discussed in comparison with the AMDP-System, which is representative for a comprehensive, multifaceted global scale. In this context, in their exemplary study, Theodoridou et al (30) investigated the concurrent validity and sensitivity to change of the 12-item Health of Nation Outcome Scales and the 3-item CGI in relation to the 100-item AMDP-System, which the authors used as a psychopathological reference scale. The correlations between the instruments were significant and plausible.…”
Section: The Amdp-system and Its Application In Research And Clinicalmentioning
confidence: 99%